Kebijakan Vaksinasi Covid-19 Berdasarkan Peraturan Presiden Nomor 14 Tahun 2021 Perubahan Atas Peraturan Presiden Nomor 99 Tahun 2020 Tentang Pelaksanaan dan Pengadaan Vaksinasi Dalam Upaya Penanggulangan Virus Covid-19 - Basar, Khoirul; Firdaus, Emilda; Junaidi, Junaidi (Peneliti.net, 2024)
In order to implement the maximum national vaccination program, President Joko Widodo issued Presidential Regulation (Perpres) Number 14 of 2021 concerning Amendments to Presidential Decree Number 99 of 2020 concerning Procurement of Vaccines and Implementation of Vaccinations in the Context of Overcoming the 2019 Corona Virus Disease (Covid-19) Pandemic. The Presidential Decree contains provisions governing the procurement of vaccines and the implementation of vaccinations in the context of dealing with the Covid-19 pandemic. Regarding administrative sanctions, it is one of the things regulated in this regulation. The administrative sanctions in question are aimed at people who have previously been declared as target recipients of the Covid-19 vaccine and basically this is contrary to Law No. 36 of 2019. People who then refuse to receive Covid-19 vaccination may be given administrative sanctions. These sanctions are stated in Article 13A paragraph (4) which states: